Динамика фракционного состава белков сыворотки крови полевки-экономки и закаспийской полевки. Сообщение II - Рогатко, И.В. (Вестник зоологии, 1975)
Peculiarities of seasonal variations in the quantitative composition of blood serum protein fractions were studied in Microtus oeconomus Pall. and M. transcaspicus Satun. Changes in metabolic reactions in certain seasons of the year affect the quantitative composition of blood serum protein fractions at different stages of the animal life. The peculiarities of changes in the above-mentioned indices are considered in different periods of a year in animals of various age groups.